2004
DOI: 10.1111/j.1468-8123.2004.00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Gas breakthrough experiments on pelitic rocks: comparative study with N2, CO2 and CH4

Abstract: The capillary-sealing ef®ciency of intermediate-to low-permeable sedimentary rocks has been investigated by N 2 , CO 2 and CH 4 breakthrough experiments on initially fully water-saturated rocks of different lithological compositions. Differential gas pressures up to 20 MPa were imposed across samples of 10±20 mm thickness, and the decline of the differential pressures was monitored over time. Absolute (single-phase) permeability coef®cients (k abs ), determined by steady-state¯uid¯ow tests, ranged between 10 À… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
123
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(145 citation statements)
references
References 14 publications
10
123
0
3
Order By: Relevance
“…Number "1" indicates the broad CO 2 mid-day peak, "2" the afternoon geogas peaks. For further details, see 4.1.3 Technical improvements regarding gas analysis Figure 8: Strip cartoon of gas breakthrough initially water saturated fractures (a) Initially water saturated fractures are not permeable to advective gas flow, (b) sporadic gas breakthrough is possible as soon as the pressure difference ∆P between the borehole and the tunnel exceeds the capillary pressure threshold P c, threshold (c) re-clogging by water due to surface tensions; (Hildenbrand et al, 2004) . Far distant seismic events (leftist "1", ~1 km) do significantly increase the calculated cumulative seismic moment, but have no effect on the borehole gas composition (not shown).…”
Section: Figures Figure 1: Conceptual Sketch Of the Secure Storage Ofmentioning
confidence: 99%
“…Number "1" indicates the broad CO 2 mid-day peak, "2" the afternoon geogas peaks. For further details, see 4.1.3 Technical improvements regarding gas analysis Figure 8: Strip cartoon of gas breakthrough initially water saturated fractures (a) Initially water saturated fractures are not permeable to advective gas flow, (b) sporadic gas breakthrough is possible as soon as the pressure difference ∆P between the borehole and the tunnel exceeds the capillary pressure threshold P c, threshold (c) re-clogging by water due to surface tensions; (Hildenbrand et al, 2004) . Far distant seismic events (leftist "1", ~1 km) do significantly increase the calculated cumulative seismic moment, but have no effect on the borehole gas composition (not shown).…”
Section: Figures Figure 1: Conceptual Sketch Of the Secure Storage Ofmentioning
confidence: 99%
“…5,19) Gas breakthrough pressure experiments using CO 2 /water or CO 2 /brine systems have mainly identified the above linear correlation between the permeability and threshold pressure for mudrocks such as clay and silt-rich rocks. 5) Furthermore, systematic experimental studies on gas breakthrough behavior of Hg/Air, N 2 /water, CO 2 /water, and CH 4 /water have been reported by Hildenbrand et al 24) They indicated that data for all the other systems of CO 2 /water also had linear correlations similar to the case of the CO 2 /water system, yet being wide variation in the measured values.…”
Section: Variation Of Threshold Pressure Depending Onmentioning
confidence: 99%
“…Low permeability formations are often of significant interest in petroleum engineering applications as they form the seal, or cap rock, above hydrocarbon reservoirs (Boulin et al 2013;Harrington and Horseman 1999;Hildenbrand et al 2002;Schlomer and Krooss 1997;Thomas et al 1968). They are important to carbon storage operations as a major trapping mechanism, specifically physical trapping (Amann-Hildenbrand et al 2013;Boulin et al 2011;Hildenbrand et al 2004;Li et al 2005;Wollenweber et al 2009Wollenweber et al , 2010. Increasingly, these systems also play a large role in the behaviour of unconventional hydrocarbon recovery processes such as shale gas operations (Javadpour et al 2007;Sakhaee-Pour and Bryant 2012).…”
Section: Introductionmentioning
confidence: 99%